Pemeriksaan Radiografi Pelvis pada Kasus Corpus Alienum Akibat Paku Tembak di Regio Gluteal - Intan Shifa Joeida; Khairil Anwar; Nursama Heru Apriantoro (Universitas Nurul Jadid, 2026)
Background: Conventional radiography remains the primary radiological procedure for suspected foreign bodies in soft tissues due to its wide availability, ease of use, and affordable, accounting for 75% of imaging examinations. In pelvic cases, the standard Anteroposterior (AP) projection alone is often insufficient for evaluating the depth of foreign body: therefore, a lateral projection is essential to provide comprehensive spatial information. objective: the study aims to describe the management of pelvic radiographic examinations using AP and lateral projections in a case of a foreign body caused by a nail gun and to assess the effectiveness of these projections in detecting radiopaque images and determining their depth. Methods: A clinical-technical case study using a descriptive observational was conducted on a 23-year-old male patient with a clinical diagnosis of a foreign body in the gluteal region. Data were collected on November 6, 2024 through direct observation of the procedure, documentation of examination techniques, radiographic results, and radiologist interpretation. Results: The AP projection successfully identified a radio-opaque shadow in the shape of a nail in the pelvic region without evidence of bone fracture. The lateral projection provided a precise depth measurement of 1.6 cm from the marker, showing a coccygeal shift of <25% of the foreign body's diameter and associated soft tissue thickening. Conclusion: The combination of AP and lateral projections is effective for visualizing radiopaque objects like nails in the gluteal region, where the lateral view is crucial for depth localization. Recommendations: Future research should conduct comparative studies on other modalities, such as Ultrasonography (USG) for radiolucent objects or 3D CT-Scan